Barriers and facilitators to high-volume evidence-based innovation and implementation in a large, community-based learning health system - Cimone Durojaiye; Stephanie Prausnitz; Jennifer L. Schneider; Tracy A. Lieu; Julie A. Schmittdiel; Smita Rouillard; Yi-Fen Chen; Kristine Lee; Douglas A. Corley (BMC, 2024)
Abstract Background Broad-scale, rapid health care change is critically needed to improve value-based, effective health care. Health care providers and systems need to address common barriers and facilitators across the evidence to implementation pathway, across diverse specialties. However, most evidence translation / implementation research evaluates single topic areas, and may be of limited value for informing comprehensive efforts. This project's objective was to identify, characterize, and illustrate common trans-topic facilitators and barriers of translating new health care evidence results to clinical implementation across multiple medical specialties. Methods This study was an evaluation of all evidence-based innovation projects completed during 2019-2021. Each project was created with medical group clinical leaders and was intended to inform clinical care. The evaluation took place in a large community-based integrated health care system, and an embedded delivery science and applied research program. Clinical investigators, scientific investigators, and clinical operational leaders received structured questionnaires regarding barriers and facilitators for the operational implementation of new research findings for each project. Responses were mapped to the Consolidated Framework for Implementation Research to identify perceived implementation barriers and facilitators. Results All 48 projects completed between 2019 and 2021 were evaluated; responses were received for 45 (94%) and 34 had comments mappable to framework domains. Potential barriers and facilitators to clinical implementation of new research results were identified across all five framework domains and, within these, the 38 constructs or sub-constructs. Among 245 total comments, the most commonly cited facilitators were how the new research evidence generated, compelled change (n = 29), specialty communication networks for disseminating results and initiating change (n = 20), leadership engagement in the project (n = 19), and the innovation's relative advantage over existing practices (n = 11). The most commonly cited barriers were inadequate resource commitment for next-step implementation (n = 15), insufficient learning/implementation culture (n = 5), and insufficient individual-level willingness/ability for change (n = 5). Conclusions A novel large-scale evaluation of barriers and facilitators across the evidence to implementation pathway identified common factors across multiple topic areas and specialties. These common potentially replicable facilitators and modifiable barriers can focus health systems and leaders pursuing large-volume evidence-to-implementation initiatives on those areas with the likely greatest benefit-for-effort, for accelerating health care change.